2019
DOI: 10.3847/1538-3881/ab0f96
|View full text |Cite
|
Sign up to set email alerts
|

TESS Full Orbital Phase Curve of the WASP-18b System

Abstract: We present a visible-light full orbital phase curve of the transiting planet WASP-18b measured by the TESS Mission. The phase curve includes the transit, secondary eclipse, and sinusoidal modulations across the orbital phase shaped by the planet's atmospheric characteristics and the star-planet gravitational interaction. We measure the beaming (Doppler boosting) and tidal ellipsoidal distortion phase modulations and show that the amplitudes of both agree with theoretical expectations. We find that the light fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
125
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(148 citation statements)
references
References 92 publications
(122 reference statements)
22
125
1
Order By: Relevance
“…Together with the other published phase curves of WASP-18 (Shporer et al 2019), WASP-121 (Bourrier et al 2019;Daylan et al 2019), and KELT-9 (Wong et al 2020b), this work underscores the TESS Mission's potential as a powerful tool for exoplanet phase curve studies. Building on the groundwork laid by similar studies in the Kepler era, TESS will greatly expand the possibilities of space-based time-domain science with its broad sky coverage: throughout the two-year Primary Mission and continuing through the recently approved Extended Mission, TESS will image almost the entire sky.…”
Section: Resultssupporting
confidence: 57%
“…Together with the other published phase curves of WASP-18 (Shporer et al 2019), WASP-121 (Bourrier et al 2019;Daylan et al 2019), and KELT-9 (Wong et al 2020b), this work underscores the TESS Mission's potential as a powerful tool for exoplanet phase curve studies. Building on the groundwork laid by similar studies in the Kepler era, TESS will greatly expand the possibilities of space-based time-domain science with its broad sky coverage: throughout the two-year Primary Mission and continuing through the recently approved Extended Mission, TESS will image almost the entire sky.…”
Section: Resultssupporting
confidence: 57%
“…WASP-100b's geometric albedo of 0.17 ± 0.05 is among the highest measured from a TESS phase curve so far, comparable to the geometric albedo of WASP-19b (Wong et al 2019) and significantly greater than that measured of WASP-18b (Shporer et al 2019) and WASP-121b (Daylan et al 2019). The albedo we measure is in line with the expectation for hot-Jupiters to have a relatively low reflectivity in the optical to near-infrared transition regime (Mallonn et al 2019) and is similar to that of several hot-Jupiters observed by Kepler (Angerhausen et al 2015).…”
Section: Wasp-100b In Contextmentioning
confidence: 54%
“…Of the three hot-Jupiter phase curves which have been observed by TESS so far (Shporer et al 2019;Daylan et al 2019;Bourrier et al 2019;Wong et al 2019), WASP-100b is the first to show a thermal phase shift indicative of efficient heat transport in its atmosphere. The magnitude of its 71 ± 4 • hotspot offset is rivaled only by the phase shift of υ Andromedae b, which has been measured to be (84.5 ± 2.3) • (Crossfield et al 2010).…”
Section: Wasp-100b In Contextmentioning
confidence: 95%
See 1 more Smart Citation
“…Such ellipsoidal deformation is predicted to produce a photometric modulation with an amplitude of ∼80 ppm. Such signals have been detected in the HAT-P-7 and WASP-18 systems using photometric time series from space-borne telescopes (Welsh et al 2010;Shporer et al 2019). Because of relative faintness of the host star (V = 11.7 mag), the ellipsoidal flux modulation in the WASP-12 system would be possible with such instruments as TESS (Ricker et al 2014) or CHEOPS (Broeg et al 2013).…”
Section: Discussionmentioning
confidence: 99%